Effectiveness of Actinomycetes Isolates from Bogor Botanical Gardens Land as Antifungal against Candida albicans Growth in Vitro - Rizqi Aminnullah (BIOEDUSCIENCE, 2020)
Background: Actinomycetes are Gram-positive and anaerobic bacteria noted for its rod-shaped forms. Actinomycetes aso has an antibiotic and antifungal activity. This study aims to identify the effectiveness of Actinomycetes isolate as the antifungal toward C. albicans growth by in vitro. Methods: Collected samples were planted on Starch Casein Agar (SCA) through pour plate method with three dilution series of 10-4, 10-5,10-6. The media used to see the obstacles zone of C. albicans was Sabouraud Dextrose Agar (SDA) with well method diffusion. Results: Actinomycetes isolates found in the samples were 15 isolates. From the three-dilution series, the study gets the size average of clear zone 3,78 mm, 4,03 mm and 3,52 mm. One way Anova (α 0,05) result also confirmed the difference of obstacles zone levels between C. albicans concentration. Conclusions: The compound comes from Actinomycetes that has potential as antifungal with one of its mechanism’s bonds ergosterol and resists fungi protein synthesis.